Aplicaciones tecnológicas de la amasadora de queso mozzarella en procesos de transformación agroindustrial. - Borja Eras, Michael Xavier (2023)
The present titling work "Technological applications of the mozzarella cheese mixer in agro-industrial transformation processes" is intended for the pedagogical use of the equipment that is located in the Dairy Research Laboratory of the Agroindustry Career at the Technical University of Cotopaxi, through the development of an operation and maintenance manual. The mozzarella mixer is designed for making cheese industrially, it has a tub with a capacity of 100 kg/h, with helical blades in the center, which rotate clockwise and counterclockwise, facilitating the spinning of the dough and optimizing the time of the process in the elaboration. A descriptive and experimental investigation is carried out for the execution of manuals, which detail the operation, care and the different types of maintenance such as: routine, preventive, predictive and corrective, required before, during and after its use with the purpose to preserve the equipment and avoid damage to it, through technical sheets after each manual for its respective verification and subsequent maintenance application, later the pedagogical practice is carried out where cleaning, starting up the equipment and safety of the user, corroborate that the information in the manuals is necessary for its correct use.